REVITALISASI PENDIDIKAN ISLAM DI ERA DIGITAL: MEMBANGUN KESEIMBANGAN ANTARA TRADISI DAN INOVASI - Maulidia Putri Aprillia; Shobah Shofariyani Iryanti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
In the digital era, Islamic education faces the challenge of maintaining traditions but keeping up with the times by following existing educational innovations. The research aims to outline the revitalization of Islamic education in the digital era to build a balance between tradition and innovation. The research method uses libraries (library research) to collect data from several literatures, such as articles and books about the revitalization of Islamic education in the digital era which can build a balance between tradition and innovation. The research results show that steps to revitalize Islamic education are carried out by using technology so that Islamic education remains viable in the digital era. Steps to revitalize Islamic education in the digital era include innovation in technology-based learning media, emphasizing an education system that masters language and skills, expanding internet access to rural/remote areas, maximizing the internal potential of Islamic education institutions by developing teacher competency, prioritizing applied science, and improving the curriculum. which unites religious and general knowledge. It was concluded that revitalization can build a balance between tradition and innovation in Islamic education.